Patient Participation in Nursing Care: Views From Ghanaian Nurses, Nursing Students, and Patients - Confidence A. Atakro MN, BSN, RN; Ernestina Armah MPH, BSN, RN; Abigail Atakro RN; Kwaku Ahenkora PhD; Stella B. Addo MPH, RN; Janet S. Aboagye MPH, RM; Alice A. Blay MPH, RN; Cynthia P. Akuoko RN; Janet Gross PhD (SAGE Publishing, 2019)
Previous studies on patient participation reported inconclusive benefits of patient participation in health care. Consequently, the World Health Organization is actively highlighting the need for the participation of patients and their families in their care. The aim of this study was to explore the views of nurses, nursing students, and patients on patient participation in Ghanaian hospitals. Sixty-five participants made up of 15 patients, 25 registered general nurses, and 25 undergraduate nursing students were involved in the study. Data collection was done through interviews and focus group discussions. Content analysis was utilized in analyzing the data to generate four main categories. These categories were as follows: (a) meaning of patient participation in Ghana, (b) patient participation encouraged more during discharge education, (c) patient participation in nursing care higher in private and smaller hospitals, and (d) perceived facilitators and inhibitors of patient participation in nursing care. Participants in this study indicated that patient participation in nursing care meant involvement of patient in treatment decisions and nursing care procedures. Participants agreed that patient participation in nursing care was mostly encouraged during discharge education. Participation was perceived to be higher in private and smaller hospitals. Wealth and higher education were perceived as facilitators of patient participation while workload and high patient acuity were perceived as inhibitors.